Characterisation of environmentally persistent free radicals and their contributions to oxidative potential and reactive oxygen species in sea spray and size-resolved ambient particles - Xinji Zhang; Fanyi Wei; Haiyan Fu; Huibin Guo (npj Climate and Atmospheric Science)
Abstract Aerosols, derived from natural processes and human activities, present various risks to the environment and human health. In this regard, the role of recent pollutant environmentally persistent free radicals (EPFRs) should not be overlooked. However, the oxidative toxicity and mass transfer processes of EPFRs in liquid-phase environments remain completely understood. In this study, the dispersion characteristics of EPFRs and their contributions to the oxidation potential (OP) and reactive oxygen species (ROS) in sea spray and size-resolved PM were investigated and compared. The results showed that the sea spray contained fast-decaying C-centred EPFRs with a half-life of 0.32 years. The concentration ranged from 0.3 × 1013 spins/m3 to 7.5 × 1013 spins/m3. It increased as the samples approached the coast. Moreover, the size-resolved PM contained slow-decaying O-centred EPFRs with a half-life of 0.51 years. The concentration ranged from 4.57 × 1013 spins/m3 to 11.46 × 1013 spins/m3, which was higher than that of most sea spray samples. The interaction between sea spray and water mainly generated hydroxyl free radicals (54 ± 3%), whereas the size-resolved PM mainly generated organic free radicals (64 ± 5%). Correlation analysis revealed that EPFRs may be involved in ROS generation. In addition, the mass transfer of EPFRs between the PM and sea spray may have been controlled by both gas and liquid films. The concentration of EPFRs at the phase interface was calculated to be 4.92 × 1013 spins/m3. In summary, EPFRs positively contribute to OP and ROS production.